The Singapore Transboundary Haze Pollution Bill in the context of ASEAN regionalism and cooperation - Varkkey, Helena (Indonesian Journal of International Law, 2018)
The Southeast Asian region has experienced transboundary haze on an almost annual basis for decades. ASEAN has been the platform for regional cooperation and collaboration for regional haze mitigation since 1985. ASEAN’s main legally-binding instrument for this purpose is the 2012 Agreement on Transboundary Haze Pollution (ATHP). Despite this, haze episodes continue to persist until present times. This paper analyses recent legal developments related to transboundary haze management among the three main affected countries; Indonesia, Malaysia and Singapore. Particularly, it examines Singapore’s Transboundary Haze Pollution Act, an extra-territorial act that extends criminal and civil liability to anyone causing or contributing to haze in Singapore. It also analyses Indonesia’s ratification of the ATHP, which followed soon after Singapore unilaterally passed their Act. Finally, it considers Malaysia’s indecisiveness in deciding its next legal move in the face of these developments among its neighbours. The ASEAN Way, a set of behavioural or procedural norms that govern regional engagement, prescribes nonlegalistic procedures and non-interference of sovereign rights, among others. This paper uses the framework of the “myth” of the ASEAN Way, popularly argued by Nischalke in 2000, to explain the changing positions of the associated states towards legal recourse related to transboundary haze. It argues that ASEAN member states can choose whether or not to adhere to the ASEAN Way in order to preserve crucial economic interests, without suffering any consequences. Hence, shifting national interests among these three states over time can likewise explain shifting attitudes and compliance towards certain ASEAN Way norms.